Development Patterns and Regional Imbalance in Brazil - Jameson, Kenneth (The Review of Economics and Statistics, 1975)
Houthakker, H. S., and S. P. Magee, and Price Elasticities in World Trade, this REVIEW, 51 (May 1969). Leamer, E. E., and R. M. Stern, Quantitative Economics (Boston: Allyn and Bacon, 1970). Magee, S. P., Prices, Income and Foreign Trade, a paper presented at the Conference on Research in Trade and Finance, Princeton, (March 1973), forthcoming in Peter B. Kenen, editor, Trade and Finance: Frontiers for Research (Cambridge: Cambridge University Press, 1974). Marston, R., Effects and Delivery Lags in British Import Demand: 1955-67, Journal of Economics, 1 (Nov. 1971). Polak, J. J., An Economic System (Chicago: University of Chicago Press, 1953). Turnovsky, S. J., International Trading Relationships for a Small Country: The Case of New Zealand, Canadian Journal of Economics, 1 (Nov. 1968).